1988
DOI: 10.1021/ja00229a053
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a cyclic form of the azide anion

Abstract: We have obtained evidence for a transient cyclic Nf anion from isotopic labeling studies. Calculations suggest that the transient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…On the other hand, K 14 N can react with 15 N 2 not only to form the addition product K 14 N 15 N 15 N but also to form K 15 N 14 N 15 N and K 15 N 15 N 14 N. This observation may indicate a K( η 3 ‐N 3 ) ion‐pair‐intermediate or transition state involving a cyclic η 3 ‐N 3 − ring in the course of the photoinduced reaction that finally rearranges to one of the three possible mixed isotopologues according to Equation . Such a transient cyclic N 3 − has already been postulated by Michl and co‐workers …”
Section: Figuresupporting
confidence: 61%
“…On the other hand, K 14 N can react with 15 N 2 not only to form the addition product K 14 N 15 N 15 N but also to form K 15 N 14 N 15 N and K 15 N 15 N 14 N. This observation may indicate a K( η 3 ‐N 3 ) ion‐pair‐intermediate or transition state involving a cyclic η 3 ‐N 3 − ring in the course of the photoinduced reaction that finally rearranges to one of the three possible mixed isotopologues according to Equation . Such a transient cyclic N 3 − has already been postulated by Michl and co‐workers …”
Section: Figuresupporting
confidence: 61%
“…Specifically, IR spectra of 15 N isotopically enriched cryogenic nitrogen matrices that had been bombarded with 5 kV Ne atoms revealed anomalous intensity patterns, implying the presence of a cyclic N 3 À . 13 Quantum chemical calculations were used to interpret these isotopic anomalies as due to the presence of cyclic 3 A 2 0 , although this isomer of the azide anion is significantly higher in energy than the bent 3 B 2 state.…”
mentioning
confidence: 99%
“…The azide radicals large electron affinity ion (EA = 2.68 ± 0.01 eV , ) means that preparation of excited electronic states of the azide ion may be possible; yet, experimental evidence for the bent 3 B 2 or cyclic 3 A 2 ′ states of the azide anion are indirect. Specifically, IR spectra of 15 N isotopically enriched cryogenic nitrogen matrices that had been bombarded with 5 kV Ne atoms revealed anomalous intensity patterns, implying the presence of a cyclic N 3 – . Quantum chemical calculations were used to interpret these isotopic anomalies as due to the presence of cyclic 3 A 2 ′, although this isomer of the azide anion is significantly higher in energy than the bent 3 B 2 state.…”
mentioning
confidence: 99%
“…An I5N labelling study of the reaction showed ' that the situation was considerably more complicated than this. Reaction (1) involves a rate-determining N-nitrosation process and hence the expected distribution of tracer is shown in (4) and (9, the pattern for (5) having previously been I5NH2l5NH2 + H N 0 2 -['SNH2'5NHNO] + H2O -H["N"NN] + H 2 0 (4) H['5N15NN] + H N 0 2 -0.5I5N2 + 0.5I5NN + 0.515NN0 + 0.5NNO + H,O (5) established by Clusius and Effenberger4 as consistent with the breakdown of nitrosyl azide, NNNNO. However, the pattern of tracer distribution was much closer to 0.33' 'N2, 0.67' 5NN, 0.67' 5 N N 0 and 0.33% NNO.…”
mentioning
confidence: 76%